2018
DOI: 10.1186/s10020-018-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Transient Receptor Potential Melastatin 3 ion channel function in natural killer cells from Chronic Fatigue Syndrome/Myalgic Encephalomyelitis patients

Abstract: BackgroundChronic Fatigue Syndrome (CFS)/ Myalgic Encephalomyelitis (ME) is a debilitating disorder that is accompanied by reduced cytotoxic activity in natural killer (NK) cells. NK cells are an essential innate immune cell, responsible for recognising and inducing apoptosis of tumour and virus infected cells. Calcium is an essential component in mediating this cellular function. Transient Receptor Potential Melastatin 3 (TRPM3) cation channels have an important regulatory role in mediating calcium influx to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(84 citation statements)
references
References 68 publications
13
57
0
1
Order By: Relevance
“…Therefore, a disturbance to calcium signalling could contribute to pathological outcomes involving immune system or bioenergetic dysfunction, both of which have been implicated in ME/CFS. In addition to the previous evidence of altered surface proteins on NK cells from ME/CFS patients, a reduction in the expression of transient receptor potential melastatin 3 (TRPM3) calcium ion channels [79] has been reported in a subpopulation of ME/CFS NK cells [80][81][82]. The reason for the reduced expression of TRPM3 in these cells is unknown but in other cell types, expression of TRPM3 is repressed by the activity of microRNA-204 (miR-204), encoded by intron 6 of the TRPM3 gene [83].…”
Section: Calcium Signallingmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, a disturbance to calcium signalling could contribute to pathological outcomes involving immune system or bioenergetic dysfunction, both of which have been implicated in ME/CFS. In addition to the previous evidence of altered surface proteins on NK cells from ME/CFS patients, a reduction in the expression of transient receptor potential melastatin 3 (TRPM3) calcium ion channels [79] has been reported in a subpopulation of ME/CFS NK cells [80][81][82]. The reason for the reduced expression of TRPM3 in these cells is unknown but in other cell types, expression of TRPM3 is repressed by the activity of microRNA-204 (miR-204), encoded by intron 6 of the TRPM3 gene [83].…”
Section: Calcium Signallingmentioning
confidence: 90%
“…However, the opposite was observed when Ca 2+ levels were assayed by flow cytometry using Indo1, a Ca 2+ -sensitive fluorescent dye in the TRPM3-depleted NK cells [80]. Subsequent studies using whole cell patch clamping, however, have reported loss of PregS-stimulated Ca 2+ responses [81,82].…”
Section: Calcium Signallingmentioning
confidence: 99%
“…The BOLD response is determined by neurovascular coupling (NVC) which consists of an initial feedforward mechanism of glutamate activation of a Ca 2+ dependent signalling pathway in both neurons and astrocytes to release vasoactive factors to increase local blood flow, and secondary feedback driven by metabolism [77]. Several recent studies have demonstrated that Ca 2+ mobilisation is impaired in ME/CFS from genetic [78,79], molecular biological [80], and electrophysiological aspects [81]. These observations would suggest, it is plausible that glutamate-Ca 2+ NVC pathways in patients with ME/CFS may be impaired because of reduced TRPM3 activity and Ca 2+ mobilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial processes including respiratory function are Ca 2+ -dependent, cytosolic Ca 2+ levels influence uptake by mitochondria through Ca 2+ -dependent channels [37,38]. Disruption of Ca 2+ channel function, specifically transient receptor potential melastatin 3, has been implicated in ME/CFS/SEID patient NK cell pathology resulting in decreased Ca 2+ mobilization [39,40]. As Ca 2+ is fundamental for many NK cell processes including cytotoxicity, NK cell function is consequently impaired [39,40].…”
Section: Discussionmentioning
confidence: 99%